Epidemiological investigation into cases of yellow fever in the North- west region of S. Paulo State, Brazil - Coimbra, Teresinha Lisieux M.; Iversson, Lygia Busch; Spir, Marlene; Alves, Venâncio A. Ferreira; Boulos, Marcos (Revista de Saúde Pública, 1987)
An epidemiological investigation was carried out in the North-west region of the State of S. Paulo of Brazil with the purpose of clarifying three suspected cases of yellow fever that occurred in people resident in the area. In this region the presence of Aedes aegypti had been verified. It was concluded that the patients had contrated yellow fever during a trip to the forested region of the Mato Grosso State, where there are enzootic cycles of the virus. Despite of the presence of Ae. aegypti, no evidence of yellow fever transmission in the local population was detected. MAC ELISA (enzyme-linked immunosorbent assay with capture of IgM antibodies) proved very useful in the rapid diagnosis of suspected cases and in the serological investigation among the relatives, neighbors and schoolmates of the patients, providing additional support for the traditional techniques.